John Ross (1777-1856) - Neatby, L.H. (ARCTIC, 1984)
The space accorded John Ross in the history of th Canadian Arctic is out of proportion to his achievement, circumstances arising from his invincible self-confidence and refusal to admit error. When convicted of blunders - obvious but excusable - he retorted on his critics with a repetitive bitterness that added much to his celebrity, although it did little for his reputation. His first unlucky arctic voyage at least restored the faded character of William Baffin; his second was a miracle of survival. In retrospect, its drama was a little dulled by Ross's tedious and wordy narrative, but it exemplified his leadership and undaunted courage. Ross's combativeness probably helped his popularity, and his futile voyage, at the age of 73, to the rescue of John Franklin won him admiration and respect. .